2021
DOI: 10.1097/wno.0000000000001134
|View full text |Cite
|
Sign up to set email alerts
|

Teprotumumab in Clinical Practice: Recommendations and Considerations From the OPTIC Trial Investigators

Abstract: Background: Thyroid eye disease (TED) is a visionthreatening and debilitating condition that until very recently had no Food and Drug Administration (FDA)approved medical therapies. Teprotumumab has recently been approved to treat TED. We aim to provide guidance for its use, based on the input of the US investigators who participated in Phase 2 and Phase 3 clinical trials. Methods: An expert panel was convened on October 11th and November 16th of 2019. All panel members had extensive experience as investigator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…Hyperglycemia was reported in 10% of patients, regardless of if they were diabetics or not. However, these values were controlled with medication and diet adjustment and levels returned to baseline after completion of teprotumumab in all patients ( 11 ). Hearing impairment was also reported in five patients, which all resolved ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hyperglycemia was reported in 10% of patients, regardless of if they were diabetics or not. However, these values were controlled with medication and diet adjustment and levels returned to baseline after completion of teprotumumab in all patients ( 11 ). Hearing impairment was also reported in five patients, which all resolved ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials have demonstrated that patients tolerate teprotumumab well ( 11 ). Most adverse effects (AEs) were transient and resolved while patients continued in their study group ( 4 , 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 124 ] It is administered via an intravenous route and is contraindicated in patients with inflammatory bowel disease or poorly controlled diabetes, pregnant or nursing patients, prepubertal children, and those on concomitant biologics. [ 125 ] In addition, recent data have highlighted the potential risk of other adverse events, including hearing loss[ 126 127 128 129 ] and cognitive decline[ 130 ] as well as recurrence of TED symptoms in a subset of teprotumumab-responsive patients[ 124 ] [see Fig. 4 ].…”
Section: Treatment Of Active Tedmentioning
confidence: 99%